Pengaruh Peran Emotional Blackmail, Incentives And Reward, dan Job Satisfaction Terhadap Tingkat Turnover Intention Pada Karyawan Generasi Z di Era Digital - Astari, Aulia Putri; Lestiani, Irne; Emilisa, Netania (Peneliti.net, 2024)
The role of generation Z in the digital work environment shows important significance in the company's success. Factors such as emotional blackmail, incentives and rewards, and job satisfaction are in the spotlight because they are related to the high turnover intention rate in generation Z. Surveys show that about 40% of generation Z and 24% of millennial employees plan to leave their jobs in the next two years. Emotional blackmail, which occurs when individuals use emotional pressure to achieve their goals, can affect the dynamics of the work environment. Generation Z tends to look for clear incentives and rewards, while job satisfaction is an important factor. This study aims to analyze the impact of emotional blackmail, incentives and rewards, and job satisfaction on the turnover intention rate in generation Z. The data analysis method involves descriptive statistics and Structural Equation Model (SEM) using SPSS and AMOS software. The results showed that emotional blackmail had a negative influence on job satisfaction, while incentives and rewards had a positive influence. Job satisfaction, in turn, has a negative influence on turnover intention. These findings provide important insights for human resource management in designing policies to maintain generation Z employee satisfaction and engagement. Managerial implications include the implementation of emotional management, optimization of incentives and rewards, and focus on job satisfaction. Although this research made an important contribution, limitations on the application and methods of the study need to be noted. Further research may involve follow-up studies, application of organizational policies, and inter-industry comparative studies to deepen understanding of these factors in a broader context.